VOICE AND CONTROL STRUCTURE IN JAVANESE: A LEXICAL-FUNCTIONAL APPROACH - Subiyanto, Agus Subiyanto (e-Journal of Linguistics; Vol. 7. Juli 2013 No. 2)
In Javanese control constructions, the controller can be the SUBJ or the OBJ of a matrix clause. When the control verb is transitive, then the OBJ usually becomes the controller, and when it is intransitive, the SUBJ is the controller. However, Javanese also has a construction involving the clitic tak- or kok-, which is used for a first or a second person Agent. This clitic construction raises some questions related to the termhood of the Agent and the argument structure of the verb having the clitic as one of its argument. With a lexical-functional approach, this paper aims to discuss voice selections in Javanese control constructions. In the analysis, the model of a syntacticised argument structure adopted from Arka and Manning (1998) and Arka (2003) was applied. This paper used the data of the ngoko (low) register of standard Javanese. The analysis shows that Javanese has three types of voice, which are active voice (AV), passive voice (PV) and objective voice (OV).  Voice alternations in Javanese control constructions occur when the matrix verb belongs to the verbs of the influence type. In this case, a transitive matrix verb in the AV form may alternate with the PV form or the OV form. The OV form is used when the Agent is a first or a second person. The OV form and the AV form are both transitive, and so they have the same argument structure. However, these two transitive forms have different mapping in the functional structure.
Keywords: voice, control structure, Javanese, lexical-functional grammar